2014
DOI: 10.1016/j.sbspro.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Interpreting Literary Texts: Difficulties of 4th Year ELT Students at a Turkish University

Abstract: This study aimed at identifying the difficulties of ELT students in analysing literary texts such as short stories and poetry in 'Selections from Western Literature' Elective Course at a Turkish university. Qualitative case study methodology was employed for understanding the students' difficulties and experiences. 42 students, who were in the 4th (final) year of their training programme participated in the study. Data were collected through the presentation check lists kept by the lecturer during student pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The message and themes become unclear since they have weak foundations in basic English to begin with When I had my literature reading, it shows that there were similar studies conducted about processing literary texts. A study from Yavuz (2014) as cited in Alkan & Günay-Erkol (2021) together with that of Afdian and Wahyuni (2020) revealed about the difficulties of international students in analyzing literary texts. It was found that the issues on processing literary texts are rooted on the poor understanding of the EFL readers on the relationship between the writer/poet, the period of the text, and the theme/s of the literary piece which are all important elements to come up with a good analysis of several literary works.…”
Section: Introductionmentioning
confidence: 99%
“…The message and themes become unclear since they have weak foundations in basic English to begin with When I had my literature reading, it shows that there were similar studies conducted about processing literary texts. A study from Yavuz (2014) as cited in Alkan & Günay-Erkol (2021) together with that of Afdian and Wahyuni (2020) revealed about the difficulties of international students in analyzing literary texts. It was found that the issues on processing literary texts are rooted on the poor understanding of the EFL readers on the relationship between the writer/poet, the period of the text, and the theme/s of the literary piece which are all important elements to come up with a good analysis of several literary works.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers tend to focus on regions such as Farida and Sinha (2014), who write about challenges of introducing English literature to Bangladeshi students. In turn, Yavuz (2014), applies his study to Turkish students. Back to Chesterman (1983), Finland becomes the region of his study.…”
Section: Introductionmentioning
confidence: 99%
“…The facilitation of learners' ability to effectively convey their ideas and insights pertaining to intercultural experiences is a central objective in the IBLL model (Tambyah, 2019;Yavuz, 2014). To achieve this, learners actively participate in the constructive phase of the IBLL learning activities.…”
mentioning
confidence: 99%